Bridging energy and metal sustainability: Insights from China's wind power development up to 2050. (15th July 2021) - Ren, Kaipeng; Tang, Xu; Wang, Peng; Willerström, Jakob; Höök, Mikael
Abstract: Concerns over anthropogenic climate change and sustainable development motivate rapid expansion of renewable energy in China. This paper explores metal demand caused by projected wind power developments in China up to 2050. Dynamic material flow analysis is combined with explorative energy scenarios to evaluate induced demand of base metals (copper, steel, aluminum, nickel) and rare earth elements (neodymium and dysprosium). The results indicate that annual demand of base metals for Chinese wind power is up to 12 times larger in 2050 than in 2018, and the cumulative demand is up to 23 times larger. Copper and nickel show greater supply pressure than aluminum and steel in the wind power sector. Cumulative copper and nickel demand of wind power sector are 9–11.9 Mt and 2.1–2.8 Mt respectively, which corresponds to 35–45.9% of copper reserves and 74–101% of nickel reserves in China. For rare earth elements demand, more than 18-fold increases are expected for annual demand in 2050 compared with 2020, and cumulative demand of neodymium and dysprosium are 1.6–3.3% and 1.4–2.8% of their reserves respectively. Recycling will play an important role after 2050 as a secondary supply of metal for Chinese wind power, and lacks noteworthy impacts on short-term future outlooks. Highlights: Technology uncertainties determine metal demand and influence metal supply risks. Nickel, copper and REEs play critical role in Chinese wind power deployment. EoL recycling enables increase of China's long-term secondary supply of metal. To achieve energy-metal system's co-benefits needs system nexus thinking.